The causality study of customer focus, work designs and occupational health and safety on worker productivity in Philippines textile industry - Tseng, Ming-Lang (Animo Repository, 2006)
The causality research objective is to identify the relationships among occupational health and safety on body (OHSB), occupational health and safety on emotion (OHSE), workstation design, feedback to management and worker productivity under intensified customer focus textile firms. Using the data of a survey of 55 firms from the Philippines customer focus textile industry, tested with internal consistency, the cronbach's alphas presented customer focus (0.772), OHSB (0.916), OHSE (0.710), workstation design (0.720), feedback to management (0.701) and worker productivity (0.721). There are obvious positively relevance between the OHSB, OHSE, workstation design, feedback to management and worker productivity under intensified customer focus environment firms. ANOVA result indicated that the Age was relatively more sensitive on the group of age 18-24 and 25-29 to the effects on OHSB and worker productivity. The Regression resulted that the customer focus factor was impacted on OHSB , OHSE, feedback to management and workstation design. This research contributes to the existing theoretical framework of OHS and worker productivity impacted under customer focus factor. Our results suggest that customer focus factors are associated with the OHS work design and worker productivity.